Why Is Rehabilitation Assistance Policy for Children With Disabilities Deviated in Supply-Demand? A Case Study in Mainland China - Qi, Cai Yun; Wang, Yuan (Frontiers in Public Health, 2021)
Children with disabilities have most potential for salvage rehabilitation, and their rehabilitation results are concerned with their entire life process. Although the Chinese state has established a targeted Rehabilitation Assistance System for Disabled Children and has expanded the provision of rehabilitation services, a severe deviation between supply and demand remains. Existing studies have focused relatively more on policy content and less on the policy context, at the macro-structural level. However, using the case of the ZW Rehabilitation Center in City J, this study divided the deviation into exclusion errors and inclusion errors, and used the policy context approach to explore the reasons for the deviation. We found that the behaviors of the participants in rehabilitation services exist in a dynamic interaction between the regulatory context, the normative context, and the cognitive context. The joint forces of the three contexts produce both exclusion errors and inclusion errors, which are the underlying reasons for the inaccurate execution of the targeted policy. The results of this research can provide enlightenment for improving rehabilitation policy.